College writing skills with readings - Langan, John; Albright, Zoe L. (McGraw Hill, 2023)
"College Writing Skills with Readings is designed to help students gain the strong foundational skills that they need to succeed in college and in their lives beyond college. It does this by focusing on the four bases of unity, support, coherence, and sentence skills; emphasizing writing for personal, academic and workplace writing; and focusing on information literacy and research writing"--